Thin Film Gas Sensors Detecting Hydrogen Peroxide - Aroutiounian, Vladimir M. (New Trends in Physical Science Research Vol. 8, 2022)
The results of studies of many types of semiconductor H2O2 sensors are discussed in this review. The properties of electrochemical detectors, sensors based on organic and inorganic materials, graphene, and nano-sensors are analyzed. Optical and fluorescent sensors, detectors made of porous materials, quantum dots, fibers, and spheres are briefly discussed. The results of our studies in the YSU of hydrogen peroxide sensors made from solid solutions of carbon nanotubes with semiconducting metal oxides are also presented in the review. The fundamentals of the manufacture of biomarkers of respiration containing hydrogen peroxide vapors, which make it possible to judge the degree of a person's illness with various respiratory diseases (asthma, lung cancer, etc.), are discussed.